Implementasi Kurikulum Merdeka Pada Pembelajaran IPAS Kelas IV SD - Yati, Iffah Mardi; Suprapti, Sri; Putri, Annisa Fitri Setiyanto; Nuraini, Ira Ayu Fitri; Nafi`ah, Likmatun; Nuryani, Wiwik Putri; Abadiyah, Af’idatul; Fitriyah, Fatih Luth (Journal of Elementary Education Research, 2023)
This study aims to analyze the implementation of the Merdeka Curriculum in science and social learning (IPAS) for Grade IV at Kauman Pati Islamic Elementary School in the 2023/2024 academic year. A qualitative case study approach was employed, with data collected through interviews (4 informants: principal, teacher, students), observation, and documentation. Key findings include: (1) Successful curriculum implementation through analysis of Learning Outcomes (CP), formulation of Learning Objectives (TP), and Learning Pathway Designs (ATP). Differentiated learning was applied according to student needs, supported by diagnostic, formative, and summative assessments; (2) Challenges included time constraints in module preparation, inadequate facilities, and adapting teaching aids; (3) Solutions involved utilizing government guidelines, expanding references, and developing creative methods and teaching tools. The findings highlight the necessity of systemic support and stakeholder collaboration for curriculum optimization. This research contributes practically to the development of Merdeka Curriculum-based science and social learning in religious-based elementary schools.